LITERATURE REVIEW ON ANALYSIS & DESIGN GIRDER BRIDGE BY USING CSI BRIDGE - Mohd Junaid Mohd Zubair,; Prof. Arvind B. Vawale,; Prof. Nitin S. Vaidkar, (International Journal of Innovations in Engineering Research and Technology, 2021)
Forimportantandsignificantreasons,thedesignof bridges has become very important. Bridges are in favour of improving the road network. Bridges not only help in the flow oftrafficwithoutinterruptionbutalsomaintainthesafetyofthe roads.Tochecktheweatheradoptedsectionwillperformsafely and satisfactorily during the life time of the structure. The bridge designs are compared with different countries design codes and determined which is better and economical. The study shows combination of various loads and sections of girdersusedtodistributeload.thedepthofbeamdecreases,the prestressing force decreases and no of cables decreases attributable to prestressing, additional strength of concrete is used and additionally well governsusefulness.